Islam and Bugis in West Kalimantan - Patmawati Patmawati; Nurfaidah M. (Al-Albab, 2015)
The Bugis people generally have tough character because of maritime and competitive traditions, as well as sufferings as a result of the colonialism. They also strongly uphold their honor. In West Kalimantan, the Bugis are also identical with Islam. The history of the arrival of the Bugis people in West Kalimantan can be traced, at least, to three stages which will be covered in this paper, namely in 1667 during the Treaty of Bungaya, and in late1946 through early 1947 when there was mass murder where 40,000 people were killed, and in 1950 when there was a revolt of DII/TII led by KaharMuzakkar. A year later, the migration happened because they were looking for a job as a civil servant (PNS). The role of the Bugis in the spread of Islam in West Kalimantan is known through education conducted by To-Panrita, To-Sugi, To-Warani, dan To-Sulasena.